The Impact of Leadership and Quality Assurance on Organizational Performance of Private Universities in Banten - Subai Subai; Syadeli Hanafi; Soleh Hidayat (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Leadership and quality assurance are two crucial components that play a role in the success of an organization, especially in higher education. Both have a close relationship and have a major influence on improving institutional performance. This study aims to explore the impact of leadership and quality assurance on organizational performance in private universities in Banten. The research method used is qualitative, with data collection conducted through observation and literature study. Once the data was collected, the analysis was conducted through several steps, including data filtering, data presentation, and conclusion drawing. The results showed that leadership and quality assurance are interrelated and mutually supportive. Strong leaders play a role in encouraging the implementation of an effective quality assurance system. On the other hand, a good quality assurance system also provides support to leaders in carrying out their job responsibilities. Both contribute significantly to improving the performance of private universities in Banten. Therefore, it is important to integrate leadership and quality assurance in all academic and non-academic activities. The implications of this study suggest that private universities in Banten should consider leadership development programs and robust quality assurance mechanisms as part of their strategic planning to drive sustainable performance improvements. Furthermore, policymakers in higher education could leverage these findings to formulate guidelines that reinforce the synergy between leadership and quality assurance across institutions, thereby enhancing overall educational standards and competitiveness.